Transclasses: Theory of social non-reproduction - Jaquet, Chantal; Elliott, Gregory (London, UK; New York, USA: Verso, 2023)
"Aims to understand the passage from one social class to another and to forge a method of approaching these particular cases which remain a blind spot in the theory of social reproduction"--
"First published as Les transclasses ou la non-reproduction © Presses Universitaires de France 2014"--Title page verso.
Includes bibliographical references and index.
Keywords: Social mobility -- France; Social stratification -- France; Philosophy; France -- Social conditions